Immunohistochemical identification of peptide hormones in the endocrine cells of the gastrointestinal tract of the Oreochromis niloticus - Tarakçi, BG; Köprücü, SS; Köprücü, K (Tubitak Scientific & Technological Research Council Turkey, 2005)
The endocrine cells of gastrointestinal tract of the Oreochromis niloticus were investigated using immunohistochemical techniques. 8 antisera were tested and 3 immunoreactivities were detected: Serotonin, glucagon and somatostatin immunoreactive cells. Substance P, insulin, gastrin, calcitonin gene related peptide (CGRP) and calbindin immunoreactive cells were not found.
Keywords: Oreochromis niloticus; immunohistochemical techniques; endocrine cells; gastrointestinal tract